Lee's Tarnished Lieutenant - Piston, William Garrett (Book collections on Project MUSE., 1987)
N the South, one can find any number of bronze monuments to the Confederacy featuring heroic images of Robert E. Lee, Stonewall Jackson, J.E.B. Stuart, and many lesser commanders. But while the tarnish on such statues has done nothing to color the reputation of those great leaders, there remains one Confederate commander whose tarnished image has nothing to do with bronze monuments. Nowhere in the South does a memorial stand to Lee's intimate friend and second-in-command James Longstreet.